The 'proper' way to spread ideas through social media: exploring the affordances and constraints of different social media platforms as perceived by Italian activists. Issue 3 (3rd May 2016) - Comunello, Francesca; Mulargia, Simone; Parisi, Lorenza
Abstract: Social media have become a relevant arena for different forms of civic engagement and activism. This article focuses on the affordances and constraints of different social media platforms as they are perceived by Italian activists. Instead of focusing on single protest movements, or on single platforms, we adopt a media ecological approach and consider a variety of environments where people can choose to express protest‐related content. Our main goal is to explore whether, and how, the affordances and constraints of different social media platforms are perceived by users, and how such perceived differences are integrated in everyday social media activities. To this end, we combined in‐depth interviews with an adapted version of the cognitive walkthrough and thinking aloud techniques. Respondents reported that they act on social media platforms according to specific representations of what each platform 'is', and how it works. Such perceptions affect users' protest‐related social media practices. Although they perceive major social media platforms filtering strategies and are aware, to different extents, of their commodified nature, they report continuing to use them for activism‐related communication, often adopting an instrumental approach.